Analysis of the Pathological Progression of Severe Community-Acquired Pneumonia Based on Serum Inflammatory Markers HMGB-1, IL-1β, and IL-6: A Propensity Score Matching Study: Serum Inflammatory Markers in Severe Community-Acquired Pneumonia - Zhang, Junwei; Liu, Tong; Xi, Wei; WuLiJie, BaYaEr; Qiu, Lingyun; Shuai, Jianjun; Yang, Fan; Wang, Xingang (Journal of Medical Biochemistry, 2025)
Objective: This study aimed to evaluate the involvement of serum inflammatory markers—high-mobility group box 1 (HMGB-1), interleukin-1β (IL-1β), and interleukin-6 (IL-6)—in the pathological progression of severe community-acquired pneumonia (SCAP), examine their association with computed tomography (CT) scores, and assess their combined utility for diagnosis and outcome prediction. Methods: We performed a propensity score-matched retrospective cohort study involving 164 SCAP patients (research group) and 164 age- and sex-matched healthy controls (control group) enrolled between March 2024 and January 2025. Serum HMGB-1, IL-1β, and IL-6 concentrations were quantified by enzyme-linked immunosorbent assay (ELISA), while pulmonary radiographic findings was evaluated using the Acute Exacerbation of Idiopathic Pulmonary Fibrosis (AE-IPF) scoring system. Comparative analyses of inflammatory markers and CT imaging findings were conducted, with subsequent correlation studies, receiver operating characteristic (ROC) curve analysis, and multivariate regression modeling to determine their relationship with in-hospital mortality. Results: Following propensity score matching, demographic characteristics were well-balanced between groups (standardized mean differences <0.1). SCAP patients demonstrated significantly elevated serum levels of HMGB-1, IL-1β, and IL-6 (P<0.05), along with higher CT scores than controls. Strong positive correlations were observed between inflammatory marker concentrations and CT scores (P<0.05). The combination of inflammatory markers and CT scoring showed enhanced diagnostic discrimination for SCAP (area under the curve [AUC]=0.9342) and superior predictive value for in-hospital mortality (AUC=0.9348) compared to individual parameters (P<0.05). Multivariate analysis identified the elevation of these biomarkers as independent predictors of mortality in SCAP patients (P<0.05). Conclusion: HMGB-1, IL-1β, and IL-6 play pivotal roles in promoting SCAP progression by driving inflammatory cascades and pulmonary tissue injury. The integrated assessment of these biomarkers with CT scoring significantly improves disease monitoring and prognostic assessment accuracy, potentially guiding individualized anti-inflammatory interventions in SCAP management.